Social Policy of Enterprise as Factor of Personnel Involvement - V. I. Sharin; M. I. Plutova (Вестник Российского экономического университета имени Г. В. Плеханова)
Enterprises still face the problem of shaping loyal and involved behavior of employees, which can affect economic results of the company work. The article shows the impact of in-company corporate social policy on employees’ involvement. The authors studied social policy of the enterprise and assessed its influence on shaping behavior of personnel involvement; they also highlighted the impact of conformity of social welfare measures and employees needs in shaping involvement relations. The research was carried out by using a whole complex of academic methods, such as system analysis, generalization and systematization of theoretical and practical data. The foundation of the empiric base was formed by findings of the research done in 2023 concerning the impact of corporate social policy of the company TMK CHERMET on workers’ involvement. The obtained information gave an opportunity to draw a conclusion about the positive effect of the availability of corporate social policy on workers’ involvement. The most serious influence of involvement is exercised by such measures of social welfare as help in improving housing conditions, granting 50% discount on food in the canteen, finance assistance in difficult circumstances. However, a third of respondents assessed certain measures as having no influence on involvement, which could be improved by including relevant measures of social welfare in corporate social policy. Therefore, the hypothesis that corporate social policy at the enterprise can increase the level of workers’ involvement by conformity of measures of social welfare offered by the enterprise and their individual needs found confirmation. The authors gave definition of the notion ‘corporate social policy’.